Some questions criminal judicial action in matters of minor. (Journal of actual problems of jurisprudence, 2016)
The aim of this scientific research is consideration of basic questions realization criminal judicial action in matters of minor presently. Were investigational and the analysis of reasons is conducted criminal act of minor. Reasons are considered offence minor from a social and psychological side. Also, the features of application of measures areconsidered suppression of criminal acts minor. An issue is discussed about the features of providing of protection of legal rights and interests minor.
Keywords: minority; offence; case; court of minor; crime